(untitled) (Journal of the College of Education for Women, 2019)
The learner has face difficult in learning if not accompanied by strong motivation and directed towards the goals that set for himself,as the type of goals set by the learner for himself is behind the difference in achievement of the tasks and levels of learning, and these goals are directed and determine his behavior Academic in the way of his study and his direction towards the lecture and colleagues. Current research aims: Build tools for thegoal orientations Measuring the goal orientations for the university studentsaccording to variables (type/class/specialization). In order to achieve the objectives of the research, a tool was constructed for the (the Goal orientation), and the psychometric properties of the tool were extracted. The validity was achieved by the retest method for the completion of the pitch (0.89), after the performance / feet (0.90) and after the performance / volume (0.85), either in the alfa-cronbach method was (0.80) for the first dimension, and (0.78) for the second dimension, and (0.86) for the third dimension. The scale was applied to a sample of (377), After collecting and processing the data statistically Data processing statistically the current research shows that university students have goal orientations, the current research recommends that the quality of the goals adopted by university students be taken into consideration.